PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP MINAT BELI LAPTOP ASUS PADA MAHASISWA FAKULTAS EKONOMI DAN ILMU SOSIAL UNIVERSITAS SARI MUTIARA INDONESIA - Haloho, Elizabeth; Ginting, Maretta; Sirait, Ronnie Togar Mulia; Pasaribu, Eva Solita (UNIKA Santo Thomas, 2024)
The aim of this research is to determine and analyze product quality and price, which have a positive and significant effect, either partially or simultaneously, on the interest in purchasing Asus laptops among students at the Faculty of Economics and Social Sciences, Sari Mutiara University, Indonesia. The research method used is a quantitative descriptive research method. The population in this study were consumers, totaling 375 students using Asus laptops. The technique for determining the sample in this research used Simple Random Sampling with a sample size of 100 respondents using the Slovin approach. The data measurement scale in this study uses a Likert scale. The data analysis techniques used are instrument testing, classical assumption testing, multiple linear regression analysis, hypothesis testing and coefficient of determination testing (R2). The results of the research show that (1) the Product Quality variable has a positive and significant effect on buying interest, (2) the Product Quality Variable has a positive and significant effect on buying interest, and (3) the Product Quality and Price variables have a simultaneous positive and significant effect on buying interest .